PERANAN TIGA SUMBER MULSA TERHADAP BEBERAPA SIFAT FISIKA ULTISOL DAN HASIL JAGUNG SEMI (Zea mays L)” - Asmar Asmar; Adrinal Adrinal (Jurnal Solum, 2006)
A research about the role of three sources of mulch on soil physical properties of Ultisol and yield of baby corn was conducted on experimental farm, Faculty of Agriculture, Andalas University and at soil laboratory of Andalas University and University of Jambi.  The research was aimed to evaluate three mulch sources (paddy straw, coconut fibre, and used paper) on several soil physical properties of Ultisols and babby corn yield. The results showed that mulch applied did not affect babby corn yield and soil physical properties of Ultisol except on plant available water.  In addition, paddy straw mulch gave better effect to soil physical properties of Ultisols and babby corn yield compared to the others.Key Words: Mulch, paddy straw, coconut fibre, used paper, Ultisols